Popularization of improved Mustard (Brassica juncea L.) production technology through frontline demonstrations in Pali district of Rajasthan - Saroj Kumari, Nishi Sethi and Joginder Singh Malik, (Indian Journal of Extension Education, 2018)
The information and communication technologies like radio, TV, newspapers, telephones and magazines are playing a major role in sustainable agricultural development since early decades and now the modern ICTs as mobiles and computers and have created a revolution. Kisan mobile advisory service (KMAS) was launched for sending agricultural information through Short Message Service (SMS). The present study was undertaken to assess the impact of message in terms of information input, process and output delivered through mobile based advisory services (MBASs) by KVKs. Out of all, 12 Krishi Vigyan Kendras (KVKs) used mobile based advisory services (MBASs). Among them , two KVKs - Fatehabad and Sirsa were randomly selected for the assessment of impact. Out of that list, 150 registered farmers were selected randomly from each KVK, comprising total sample of 300 registered farmers. The overall information output pattern of the mobile based messages as received by registered farmers was found to be medium (61.00%) followed by high (23.67%) and low (15.33%) information output pattern